LETHALITY AND ANTIMICROBIAL SCREENING OF SEA HARE (Dolabella auricularia) INK AGAINST THE FISH PATHOGENS - JR., FABIO C. RUAZA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
This study determined the potential of sea hare’s (Dolabella auricularia) ink as a microbial agent in fish pathogens. The output of this study provides additional information to replace the expensive and hazardous antibiotics that are already being applied in aquaculture. Six (6) fish pathogens were tested for antimicrobial assays. The results revealed that all of the six (6) pathogens undergo growth inhibition in different concentrations. The Escherichia coli, Enterococcus faecalis, Vibrio cholera, and Staphylococcus epidermidis showed maximum activity (very active) against the Salmonella sp. and Proteus vulgaris with "partially active" observation. For the toxicity analysis for nauplii, the LC50 value is 529.12, indicating that the sea hare’s ink is moderately toxic. This is to recommend testing its bioactive secondary metabolites with the possibility of use in the enhancement of new pharmaceutical agents against aquaculture disease. A better understanding of its ink could lead us to the development of new therapeutics.